2016
DOI: 10.2174/1874210601610010099
|View full text |Cite
|
Sign up to set email alerts
|

Dental and Chronological Ages as Determinants of Peak Growth Period and Its Relationship with Dental Calcification Stages

Abstract: Purpose:To investigate the relationship between dental, chronological, and cervical vertebral maturation growth in the peak growth period, as well as to study the association between the dental calcification phases and the skeletal maturity stages during the same growth period.Methods:Subjects were selected from orthodontic pre-treatment cohorts consisting of 420 subjects where 255 were identified and enrolled into the study, comprising 145 girls and 110 boys. The lateral cephalometric and panoramic radiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 31 publications
4
16
1
3
Order By: Relevance
“…7 Although Ramos et al 7 found a weak correlation between skeletal age and chronological age, the current data showed a significant positive correlation between chronological age and skeletal growth (Figure 3). These findings agreed with Litsas and Lucchese 21 who also reported that skeletal growth was positively associated with chronological age. To date, no published studies have investigated CVMS prediction from chronological age.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…7 Although Ramos et al 7 found a weak correlation between skeletal age and chronological age, the current data showed a significant positive correlation between chronological age and skeletal growth (Figure 3). These findings agreed with Litsas and Lucchese 21 who also reported that skeletal growth was positively associated with chronological age. To date, no published studies have investigated CVMS prediction from chronological age.…”
Section: Discussionsupporting
confidence: 92%
“…19 In the present study, salivary ALP activity, protein concentration, and chronological age were investigated as biomarkers for skeletal maturation assessment since they have been associated with bone metabolism and general body growth. 20,21 The current results suggested that salivary ALP activity may have a promising diagnostic value in skeletal maturity assessment.…”
Section: Discussionmentioning
confidence: 65%
“…This means that, in our sample, the maturity growth rate decreased in proximity of this value. Similarly to what found in the literature (see Litsas & Lucchese, ; Prieto et al., ), this point was different between female, who exhibited an earlier dental maturation, and male subjects (respectively, 10.49 and 10.88 years). In order to understand the distribution of age for specific values of the predictor S , some calibrating distributions from SNBC model are reported in Figure which highlights a twofold aspect: the nonnormality of age distributions and their heteroskedasticy.…”
Section: Resultssupporting
confidence: 80%
“…(), we used the sum of open apices ( S ) as age predictor. Subject's gender have been proved to differently influence this measure (Litsas & Lucchese, ; Prieto et al., ), thus we implemented two age estimation for girls and boys separately.…”
Section: Resultsmentioning
confidence: 99%
“…The dental assessment method according to the degrees of calcification, proposed by Demirjian, 14 is considered a valid method and a world reference that can be used to compare data from different studies on this matter. 8,15,16 In the present study the mean of the differences between dental and chronological age was found to be 0.60±.44 in both sexes. Results by sex were 0.58±1.48 years in females and 0.63±1.38 years in males.…”
Section: Discussionsupporting
confidence: 49%